PFM.10 Detection of major congenital heart disease (CHD) in babies born at a UK regional perinatal centre. (9th June 2014) - Palanisami, B; Lim, J; Subhedar, N
Abstract : Background: CHD is the commonest group of congenital malformations. It has been suggested that the introduction of routine newborn pulse oximetry will improve detection rates of major CHD. Aim: We aimed to quantify the current detection rate of major CHD in babies born at a regional UK perinatal centre over a 12 month period. Methods: Information about babies diagnosed with cardiac anomalies was collected from a central cardiac database and cross-referenced against the regional fetal anomaly database. Major cardiac defects comprised 'critical' anomalies (needing intervention in the first 28 days of life) and 'serious' anomalies (needing intervention in the first year of life). Results: 154 babies were admitted to the regional cardiac centre with critical (120) and serious (34) cardiac anomalies, of whom 25 babies (16 critical and 9 serious) were born at our centre. Of these 25 babies, 19 (76%) were diagnosed antenatally (12 critical, 7 serious). A further five (25%) babies were diagnosed in the early postnatal period (3 critical, 2 serious). One baby with critical CHD was not diagnosed prior to discharge because of the need for urgent transfer for abdominal surgery. Conclusion: The antenatal detection rate of major CHD in our inborn and booked populations was 76 and 54%, respectively. High antenatal detection rates are likely to reduce the clinical and cost-effectiveness of postnatal screening interventions for major CHD. Routine pulse oximetry would not have enabled earlier diagnosis in the one baby in whom the diagnosis of major CHD was not made prior to discharge.